Fishery stock dynamics in the Baltic Sea: The dichotomy between total allowable catch limits and spawning stock biomass - Rosciszewski-Dodgson Michael J.; Cirella Giuseppe T. (Fisheries & Aquatic Life)
When managing heavily exploited fisheries, the primary objective is ensuring the long-term sustainability of stocks. Policy makers employ various measures to achieve this, with one important approach being the establishment of total allowable catch (TAC) limits for commercial fish stocks. These limits are set to maintain a target level that can sustain or rebuild the spawning stock biomass (SSB), which is an indicator of a stock’s reproductive capacity. Ideally, a strong correlation between TAC quotas and SSB exists, indicating that reductions in TAC are positively impacting SSB. However, in practice, the influence of TAC quotas on fish populations is diminished by other factors affecting reproductive capabilities. This study conducted on the eight most commercially valuable stocks in the Baltic Sea examined this relationship using statistical analysis. The findings revealed that five stocks exhibited a strong-to-moderate positive association between variables, while data for the remaining three stocks were insufficient. The results indicated that stocks with a strong correlation between TAC limits and SSB can be managed more effectively, offering greater potential for sustainability. In contrast, those without this correlation need a more holistic approach that incorporates external ecological factors, as management alone may not suffice to prevent declines. Future strategies should balance TAC and SSB while considering broader environmental factors to ensure sustainable stock dynamics.